Anti-trinitarianism in Newtons General Scholium to the Principia - Ducheyne, Steffen (European Journal of Science and Theology, 2009)
Recent findings on Newton's heretical beliefs in the five draft versions of the General Scholium, which was added to the second edition of the Principia in 1713, are discussed here. We shall use these snapshots as a tool to gain understanding into the process of composition of the theological material from the General Scholium.